Individual differences in pain sensitivity predict the experience of unfairness. (June 2019) - Wang, Haixia; Li, Kefeng; Xie, Xiaofei
Pain has shaped our evolutionary history, and pain-free experiences are critical for our health. There are, however, enormous individual differences in pain sensitivity, and the psychological consequences of this heterogeneity are only poorly understood. Here, we investigated whether individual differences in pain sensitivity predicted the experience of unfairness. We found that the magnitude of pain sensitivity correlated with the extent to which participants experienced unfairness. This association was due to the shared human alarm system of unfairness and pain sensitivity. This finding may elucidate mechanisms for producing a new and positive cycle of a healthy experience between fairness and feeling pain-free.